Pengembangan Kemampuan Kognitif Anak Berkebutuhan Khusus Melalui Pengenalan Hewan Di Pondok Pesantren Al-Achsaniyyah - Amalia, Erna; Ulya, Aisyatun Nuril; Larasati, Wulan; 'Ubudiyah, Farikhatul (Community Development: Jurnal Pengembangan Masyarakat Islam, 2025)
Developing The Cognitive Abilities Of Children With Special Needs Through Animal Introduction At Al-Achsaniyyah Islamic Boarding School. Stimulation to develop the cognitive abilities of children with special needs requires interesting and interactive learning media. Introducing animals and their habitats is one effective theme for this purpose. This community service program aims to develop the cognitive aspects of children with special needs at the Al-Achsaniyah Islamic Boarding School in Kudus through the service learning method. The activities were implemented in the form of interactive learning, including visual recognition of animals, picture guessing games, and creative activities such as making collages from origami paper pieces to enhance concentration and fine motor skills. The results of the activity showed an increase in children's enthusiasm and cognitive abilities. Specifically, children were able to recognize various types of animals, classify them based on their habitats, and demonstrate improved focus during the creativity sessions. Evaluations from the teachers stated that the media and methods used were very helpful in making the learning process more engaging, interactive, and effective in stimulating children's cognitive development.